Size, organization, and dynamics of soluble SQSTM1 and LC3-SQSTM1 complexes in living cells. Issue 9 (1st September 2016) - Kraft, Lewis J.; Dowler, Jacob; Manral, Pallavi; Kenworthy, Anne K.
ABSTRACT: Selective macroautophagy/autophagy—with the help of molecular receptors—captures cargo for lysosomal degradation. Among the best-studied molecular receptors is SQSTM1/p62, a homo-oligomeric ubiquitin binding protein, which binds to both cargo and MAP1LC3B/LC3, a protein important for autophagosome biogenesis. Although the mechanisms underlying interaction of LC3 and SQSTM1 have been extensively studied, very little is known about the size or organization of soluble complexes formed between SQSTM1 and LC3 prior to phagophore (the autophagosome precursor) binding in live cells at the molecular level. To address this question, in the current study we use a combination of 2 microscopy-based approaches, FRET microscopy and confocal FRAP, to study the nanoscale properties of soluble SQSTM1 complexes and SQSTM1-LC3 complexes in living HeLa cells. We find that, independent of puncta, SQSTM1 oligomerizes to form very slowly diffusing complexes that contain multiple copies of SQSTM1 within FRET proximity of one another. Furthermore, we show that the interactions of soluble pools of LC3 and SQSTM1 can be readily detected by both FRAP and FRET. Finally, we uncover unexpected roles of SQSTM1's PB1 domain, a region of the protein involved in homo-oligomer formation, in complex formation. Taken together, these findings provide new insights into the nature of nanometer-sized protein complexes in the autophagy pathway.